Effects of repetitive transcranial magnetic stimulation on upper extremity motor function in stroke survivors: study protocol of a randomized sham-controlled trial - Sun, Tao; Yu, Qian (Frontiers in Neurology, 2026)
BackgroundStroke is a group of diseases with neurological deficits caused by cerebrovascular lesions. Despite standard treatment, a large number of patients are left with significant upper extremity motor dysfunction. Therefore, improving upper limb motor function and promoting neurological recovery in stroke patients has become a core challenge in the field of neurorehabilitation.Methods and analysisThis study will be designed as a randomized, sham controlled clinical trial. Thirty-six patients with upper limb motor dysfunction after stroke will be included, and their Fugl-Meyer Upper Extremity Motor Function Rating Scale (FMA-UE) score will be ≤ 26 points. Subjects will be randomly assigned to the following three groups (n = 12/group): HF-rTMS: Treated with high-frequency (5 Hz) repetitive transcranial magnetic stimulation (rTMS) on the dorsal premotor cortex (PMd) on the contralesional side. Low-frequency group (LF-rTMS): Treated with low-frequency (1 Hz) rTMS on the primary motor cortex (M1) on the contralesional side. Sham control group: The stimulation target and parameter settings will be the same as those of the high-frequency group, but the coil will be placed perpendicular to the scalp plane. The intervention regimen will be rTMS treatment once daily, five times a week for 3 weeks. Outcome measures: Main outcome measures: Upper limb motor function, assessed by FMA-UE. Secondary outcomes: Barthel Index (BI), National Institutes of Health Stroke Scale (NIHSS). Exploratory indicators: fMRI data and motor evoked potential (MEP) parameters. All assessment data will be collected before and after the intervention.Communication and ethicsThis study has been reviewed and approved by the Basic and Clinical Research Ethics Committee of Sichuan Provincial People’s Hospital (Lun Shen (Yan) No. 353–1 of 2025). The results of this research will be disseminated through the network of professionals and the general public, and peer-reviewed scientific papers will be published and presented at relevant conferences.RegistrationThis trial has been registered with the Chinese Clinical Trials Registry with registration number ChiCTR2500105502.